Exploitation status of Lobster on Kebumen Waters - Suradi Wijaya Saputra (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2009)
The research of the exploitasion status of Lobster (Panullirus sp) was held on Kebumen waters Central Java. The objective research were to analysis of exploitation level and fishing season.of lobster. Samples was collected from August to September 2008, using survey methods. The study area were three TPI : TPI Pasir, TPI Argopeni and TPI Karangduwur. The results showed that Lobster caught occurred through the year, with fishing season from November to February, and peak season on December. Base on carapace length and weigh of Lobster, show that level of exploitation was indicated over-exploitation.Key word : Lobster, exploitation status, Kebumen waters